Visualising improved peritoneal perfusion at lower intra-abdominal pressure by fluorescent imaging during laparoscopic surgery: A randomised controlled study. (May 2020) - Albers, Kim I.; Polat, Fatih; Loonen, Tom; Graat, Leon J.; Mulier, Jan P.; Snoeck, Marc MJ.; Panhuizen, Ivo F.; Vermulst, Ad A.; Scheffer, Gert-Jan; Warlé, Michiel C.
Abstract: Background: Laparoscopy is the gold standard for many surgical procedures and is embraced as minimally invasive surgery in the enhanced recovery after surgery programme. Lowering intra-abdominal pressure during laparoscopy may decrease the degree of surgical injury and further enhance patient outcomes. This study aims to assess the effect of low pressure pneumoperitoneum on peritoneal perfusion during laparoscopic surgery. Materials and methods: We performed a prospective randomized intervention study in 30 adults undergoing colorectal robot assisted laparoscopic surgery at a secondary care medical center in the Netherlands between June and December 2018. A 3 min video recording of the parietal peritoneum was made with the Da Vinci® Firefly mode following intravenous injection of 0.2 mg/kg indocyanine green at a pneumoperitoneum pressure of 8, 12 or 16 mmHg. Observers were blinded for the level of intra-abdominal pressure that was used. Fluorescent intensity in [−] over time was extracted from each video in MATLAB. Time to reach maximal fluorescent intensity (TMFI) and maximum fluorescent intensity (MFI) were compared among groups. The study was registered at clinicaltrials.gov (NCT03928171). Results: Mean TMFI was shorter at low pressure (8 mmHg) than standard pressure (12 and 16 mmHg): 44 ± 12 versus 58 ± 18 s (p = 0.032), respectively. Mean MFI was higher at 8 mmHg than 12 and 16 mmHg (222 ± 25 versus 188 ± 54, p = 0.033). Regression analysis identified intra-abdominal pressure, mean arterial pressure and female gender as significant predictors of peritoneal perfusion. Conclusion: Low pressure pneumoperitoneum was associated with improved perfusion of the parietal peritoneum. Current available evidence supported feasibility and enhanced postoperative recovery. Future investigations should focus on optimizing factors that facilitate lower intra-abdominal pressure and explore effects on other clinically relevant patient outcomes such as anastomotic leakage and immune homeostasis. Highlights: Improved peritoneal perfusion at lower intra-abdominal pressure during laparoscopic surgery. Low pressure pneumoperitoneum is the cornerstone of low-impact laparoscopy. Low-impact laparoscopy can decrease surgical damage and enhance recovery after surgery.